INTER-NOISE 86 - ENGEL, Z. (Archives of Acoustics, 1987)
The 15 th International Conference Inter-Noise 86 was held on 21-23 July 1986. It was sponsored by the International Institute on Noise Control Engineering and organized by the Massachusetts Institute of Technology in Cambridge, USA.